Demographic Bonus Management Strategies In Facing The Industrial Revolution 4.0 With The Perspective Of Defense Science And State Defense - Purbaningrat, Bagaskara Wahyu; I Nengah Putra Apriyanto; George Royke Deksino (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
In the coming years, Indonesia will experience a Demographic Bonus, with the fourth largest population in the world. This phenomenon provides great opportunities for economic growth and social progress. However, the advent of the Industrial Revolution 4.0 brings new challenges related to the changing landscape of work and automation that could potentially pose a threat to the sovereignty and integrity of the Unitary State of the Republic of Indonesia. This research evaluates strategies for managing the Demographic Bonus in Indonesia by considering the implications of the Industrial Revolution 4.0 from the perspective of defense science and state defense. The method used in this research is qualitative with descriptive analysis, Data collection in this research uses a literature study, The results showed that in facing and maximizing the demographic bonus, the right strategy is needed. The government has prepared a strategy to face the demographic bonus, namely by improving the quality of human resources such as reducing the stunting rate; increasing the human development index; increasing the gender empowerment index, then adjusting the education curriculum to the needs of industry 4.0, and preparing jobs by making downstream industrial policies and carrying out infrastructure development and access to technology, especially in 3T areas, is also an important focus. From the perspective of defense science and state defense, its role has increased in identifying threats, formulating defense policies, and protecting infrastructure. Implementation evaluations show that collaboration across sectors and governments is essential. Community empowerment, family planning, and controlled population growth are also key factors. With synergy between the government, private sector, and society, Indonesia is expected to reap maximum benefits from the Demographic Bonus while managing the impact of the Industrial Revolution 4.0, promoting sustainable growth and national prosperity.